Design and testing of an anti-scattering grid for medium-energy X-ray flash radiography. (January 2016) - Liu, W.J.; Fan, C.
Abstract: We propose an effective design of a 2-mm-thick tungsten anti-scattering grid for medium-energy X-ray imaging. First, the Monte Carlo simulation is carried out firstly, which indicates that the ratio of direct to scattered radiation can reach as high as 1.54. The grid for the testing is produced using precision mechanical drilling technology, with the typical size of 52.1×52.1 mm 2 . Clear edge of the sample can be visualized in the image when the designed grid is used and the quality of the image is substantively improved. Abstract : Highlights: We design an anti-scattering grid used in medium-energy X-ray flash radiography. We perform Monte Carlo simulations to optimize the parameters of the grid. The grid for testing is produced by precision mechanical drilling technology. High-quality image with good resolution is obtained after using the as-designed grid. The as-designed grid is very thin and can be easily produced.